Pengukuran Kreatifitas Anak Usia Dini Menurut E.P. Torrance - Ulya Ainur Rofi’ah; Nur Khotimah; Putri Indah Lestari (Institut Agama Islam Nahdlatul Ulama Tuban, 2023)
This article aims to find out and understand how to measure early childhood creativity proposed by E.P. Torrents. Furthermore, the research design used is qualitative with a choice of library research methods. Creativity tests are used to identify gifted children, both verbally and figuratively to assess students' or students' divergent thinking abilities. One of the leading figures in measuring creativity is E.P. Torrents. The Torrance test to measure creative thinking (Torrance Test of Creative Thinking) can be used from preschool through high school graduation, has both verbal and figural forms. Of the two Torrance Test of Creative Thinking (TTCT) creativity tests both figural and verbal, the one most often used to measure the creativity of preschoolers or early childhood is the figural creativity test. Because verbal memory skills that rely on creativity in the form of words in preschool-aged children are very limited.